Metabolic and Genetic Properties of Petriella setifera Precultured on Waste - Oszust, Karolina; Panek, Jacek; Pertile, Giorgia; Siczek, Anna; Oleszek, Marta; Frąc, Magdalena (Frontiers in Microbiology, 2018)
Although fungi that belong to Petriella genus are considered to be favourable agents in the process of microbial decomposition or as plant endophytes, they may simultaneously become plant pests. Hence, nutrition factors are supposed to play an important role. Therefore, it was hypothesized that Petriella setifera compost isolates, precultured on three different waste-based media containing oak sawdust, beet pulp and wheat bran will subsequently reveal different metabolic properties and shifts in genetic fingerprinting. In fact, the aim was to measure the influence of selected waste on the properties of P. setifera. The metabolic potential was evaluated by the ability of five P. setifera strains to decompose oak sawdust, beet pulp and wheat bran following the MT2 plate® method and the catabolic abilities of the fungus to utilize the carbon compounds located on FF plates®. Genetic diversity was evaluated using Amplified Fragment Length Polymorphism analysis performed both on DNA sequences and on transcript-derived fragments. P. setifera isolates were found to be more suitable for decomposing waste materials rich in protein, N, P, K and easily accessible sugars (as found in wheat bran and beet pulp), than those rich in lignocellulose (oak sawdust). Surprisingly, among the different waste media, lignocellulose-rich sawdust-based culture chiefly triggered changes in the metabolic and genetic features of P. setifera. Most particularly, it contributed to improvements in the ability of the fungus to utilize waste-substrates in MT2 plate® and two times increase the ability to catabolize carbon compounds located in FF plates®. Expressive metabolic properties resulting from being grown in sawdust-based substrate were in accordance with differing genotype profiles but not transcriptome. Intraspecific differences among P. setifera isolates are described.